Societies of social innovation : voices and arguments - Gurruchaga, Ander (Sussex Academic Press, 2013)
Social innovation is a concept that is associated with a range of experiences, dimensions, and fields within the language of management and economics and in the social and productive uses of technology, and this study seeks to clarify the meanings and uses of social innovation in contemporary societies. The book looks at the historical view of social innovation and explains how advanced countries and societies construct innovative environments and conditions that can improve the future of society. It explores the significance of social innovation through civic organizations, public institutions, and social movements and its use in the reinvention of the ethics of capitalism.